2019
DOI: 10.1017/jsl.2019.83
|View full text |Cite
|
Sign up to set email alerts
|

Predicative Collapsing Principles

Abstract: We show that arithmetical transfinite recursion is equivalent to a suitable formalization of the following: For every ordinal α there exists an ordinal β such that 1 + β · (β + α) (ordinal arithmetic) admits an almost order preserving collapse into β. Arithmetical comprehension is equivalent to a statement of the same form, with β · α at the place of β · (β + α). We will also characterize the principles that any set is contained in a countable coded ω-model of arithmetical transfinite recursion resp. arithmeti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In [12] the order type of ϑ(D) has been determined for some natural WO-dilators D. For example, it has been shown that D(X) = 1 + 2 × X 2 (with an appropriate linear order) leads to ϑ(D) ∼ = Γ 0 . By the uniform independence principle we can now recover Friedman's result [16] that Kruskal's theorem for binary trees with two labels is independent of the axiom system ATR 0 .…”
Section: Introductionmentioning
confidence: 99%
“…In [12] the order type of ϑ(D) has been determined for some natural WO-dilators D. For example, it has been shown that D(X) = 1 + 2 × X 2 (with an appropriate linear order) leads to ϑ(D) ∼ = Γ 0 . By the uniform independence principle we can now recover Friedman's result [16] that Kruskal's theorem for binary trees with two labels is independent of the axiom system ATR 0 .…”
Section: Introductionmentioning
confidence: 99%
“…. , z k , the order on ω 2 (Z ) is characterized by the following clauses (as before Theorem 2.2 in [24]):…”
Section: Introductionmentioning
confidence: 99%
“…For an ordinal α and a number n ∈ N, the ordinal ω α n is explained by the recursive clauses ω α 0 = α and ω α n+1 = ω ω α n (towers of exponentials in the sense of ordinal arithmetic). The resulting ordinal ω α 2 is isomorphic to the order ω 2 (1 + α) from (1.3), as shown in [24]. We now define linear orders OT 0 n by the recursive clauses…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation